Management of Late-Onset Complete Atrioventricular Block Post Transcatheter Closure of Perimembranous Ventricular Septal Defects - Xie, Lijian; Zhang, Han; Zhang, Rufang; Xiao, Tingting (Frontiers in Pediatrics, 2020)
Long-term late-onset complete atrioventricular block (CAVB) is one of the most serious complications of transcatheter closure of perimembranous ventricular septal defect (pmVSD); it can cause an Adams-Stoke attack or even sudden death. Transcatheter closure of pmVSD is not approved by the FDA, yet the procedure has proved to be a successful alternative to a surgical strategy in China. Although transcatheter closure of pmVSD is widely and successfully performed, especially in China, late-onset CAVB is still difficult to avoid. Here, we report a case with late-onset CAVB post transcatheter closure that was successfully treated. By doing so, we reassess the safety of pmVSD occluder closure and highlight that use of this procedure should adhere to more stringent indications.